DEVELOPING EMPATHIC SENSITIVITY IN YOUNGER CHILDREN - KWAŚNIEWSKA-PASZTA, SANDRA (Society Register, 2021)
The article presents a review of theoretical concepts on empathic sensitivity. The text demonstrates correlations between empathy and moral development and presents empathy in children and its conditions. The article is also aimed at pointing to the significance of empathy in human relations, and it introduces several factors which influence bringing up children to have empathy. Moreover, it presents the methods of working with children aimed at developing their empathic sensitivity. These include, among others, drama, working with literary texts and art techniques.